Basic statistics for librarians - Simpson, I. S. (London : Bingley, 1975)
The text aims to provide the basic essentials of statistics in a concise fashion, and to present them in a relatively simple form, in an attempt to make them comprehensible to all students whatever their background as well as practicing librarians and information workers.
Includes index.
Includes bibliographical references: p. 94.
rpm 29/08/2018
Loans
Keywords: Statistics